Longitudinal trajectory of cardiac magnetic resonance and cardiopulmonary exercise testing findings in moderate to severe COVID-19 and association with symptoms. (14th October 2021) - Cassar, M P; Lewandowski, A J; Mahmod, M; Xie, C; Tunnicliffe, E M; Petousi, N; Talbot, N P; Holdsworth, D; Neubauer, S; Raman, B
Abstract: Background: Cardiac magnetic resonance (CMR) and cardiopulmonary exercise testing (CPET) have provided important insights into the prevalence of early cardiopulmonary abnormalities in COVID-19 patients. It is currently unknown whether such abnormalities persist over time and relate to ongoing symptoms. Purpose: To describe the longitudinal trajectory of cardiopulmonary abnormalities on CMR and CPET in moderate to severe COVID-19 patients and assess their relationship with ongoing symptoms. Methods: Fifty-eight previously hospitalised COVID-19 patients and 30 age, sex, body mass index, comorbidity-matched controls underwent CMR, CPET and a symptom-based questionnaire at 2–3 months (2–3m). Repeat assessments (including gas transfer) were performed in 46 patients at 6 months (6m). Results: During admission, 1/3rd of patients needed ventilation or intensive care (Table 1) and three (5%) had a raised troponin. On CMR, patients had preserved left (LV) and right ventricular (RV) volumes and function at 2–3m from infection. By 6m, LV function did not change but RV end diastolic volume decreased (mean difference −4.3 mls/m 2, p=0.005) and RV function increased (mean difference +3.2%, p<0.001, Fig. 1A). Patients had higher native T1 (a marker of fibroinflammation) at 2–3m compared to controls (Table 1, Fig. 1B), which normalised by 6m. Extracellular volume was normal and improved by 6m. Native T2, a marker of myocardial oedema, did not differ between patients and controls on serial CMR. At 2–3m, late gadolinium enhancement (LGE) was higher in patients (p=0.023) but became comparable to controls by 6m (p=0.62). Six (12%) patients had LGE in a myocarditis pattern and one (2%) had myocardial infarction. None had active myocarditis using the Modified Lake Louise Criteria. Lung imaging (T2-weighted) revealed parenchymal abnormalities in 2/3rds of patients at 2–3 and 6 months. The extent of abnormalities improved on serial imaging (Table 1). Gas transfer (DLco) was worse in those with lung abnormalities (77% vs 91% of predicted, p=0.009). CPET revealed reduced peak oxygen consumption (pVO2) in patients at 2–3m, which normalised by 6m (80.5% to 93.3% of predicted, p=0.001) (Table 1, Fig. 1C). At 2–3m, 49% of patients had submaximal tests (respiratory exchange ratio <1.1), reducing to 25% by 6m (p=0.057). VE/VCO2 slope, a marker of lung efficiency, was abnormal in patients but improved on serial CPET (Table 1, Fig. 1D). Cardiac symptoms (chest pain, dyspnoea, palpitations, dizziness or syncope) were present in 83% of patients at 2–3m, reducing to 52% by 6m (p<0.001). There was no significant association between CMR or CPET parameters and persistent cardiac symptoms at 6m (Fig. 1E). Conclusions: Cardiopulmonary parameters (on CMR and CPET) improved in moderate-severe COVID-19 patients from 2–3 to 6 months post infection. Despite this, patients continued to experience cardiac symptoms which had no relationship with measured parameters. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): 1. NIHR Oxford and Oxford Health Biomedical Research Centre, Oxford British Heart Foundation (BHF) Centre of Research Excellence (RE/18/3/34214), United Kingdom Research Innovation and Wellcome Trust2. Medical Research Council and Department of Health and Social Care/National Institute for Health Research Grant (MR/V027859/1) ISRCTN number 10980107